The Effectiveness of Using Blackboard in Improving the English Listening and Speaking Skills of the Female Students at the University of Hail - Hussein, Elham T. (Advances in Social Sciences Research Journal, 2016)
The use of Learning Management Systems (LMSs) in Saudi universities has brought about significant changes in the academic environment. Therefore, the effectiveness of these systems deserves a careful examination. The current study investigates female students’ perceptions on the accessibility, usability and effectiveness of using Blackboard (Bb) in a web-enhanced listening and speaking course at the University of Hail (UoH). The study was conducted during the first semester of the academic year 2015-16. Data were collected from 37 female students at the Department of English using an attitudinal questionnaire and Semi-structured interviews in order to validate the study and elicit elaborate responses regarding the benefits of Bb, the challenges the participants’ faced and the suggestions they have for change and improvement. Statistical analysis of the data revealed that students generally had positive attitudes towards using Bb particularly because they found it helpful in improving their language skills and the student-instructor communication. Still, issues such as improving student-student communication and course design on Bb need further attention.